Checkpoint Blockade Rescues the Repressive Effect of Histone Deacetylases Inhibitors on γδ T Cell Function - Bhat, Sajad A.; Vedpathak, Disha Mohan; Chiplunkar, Shubhada V. (Frontiers in Immunology, 2018)
Histone deacetylases (HDAC) are one of the key epigenetic modifiers that control chromatin accessibility and gene expression. Their role in tumorigenesisis well established and HDAC inhibitors have emerged as an effective treatment modality. HDAC inhibitors have been investigated for their specific anti tumor activities and also clinically evaluated in treatment of various malignancies. In the present study, we have investigated the effect of HDAC inhibitors on the effector functions of human γδ T cells. HDAC inhibitors inhibit the antigen specific proliferative response of γδ T cells and cell cycle progression. In antigen activated γδ T cells, the expression of transcription factors (Eomes and Tbet) and effector molecules (perforin and granzyme B) were decreased upon treatment with HDAC inhibitors. Treatment with HDAC inhibitors attenuated the anti-tumor cytotoxic potential of γδ T cells which correlated with the enhanced expression of immune checkpoints PD-1 and PD-L1 in γδ T cells. Interestingly, PD-1 blockade improves the anti-tumor effector functions of HDAC inhibitor treated γδ T cells which is reflected in the increased expression of Granzyme B and Lamp-1. This study provides a rationale for designing HDAC inhibitor and immune check point blockade as a combinatorial treatment modality for cancer.